THE EFFECT OF PROBLEM BASED LEARNING MODEL BASED ON REACT APPROACH ON STUDENTS' 21ST CENTURY SKILLS: META-ANALYSIS - Youna Chatrine Bachtiar; Mohammad Edy Nurtamam; Tomi Apra Santosa; Unan Yasmaniar Oktiawati; Abdul Rahman (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study aims to determine the Problem-Based Learning model based on the REACT approach to students' 21st-century skills. This type of research is meta-analysis research. The data sources in the study came from the analysis of 13 international and national journals that have been published from 2018-2023. The data source search process is Google Scholar, Hindawi, Eric, ScienceDirect, Springer, and ProQuest. The inclusion criteria in this study are 1) Journals or proceedings indexed by Scopus or SINTA; 2) The type of research is experimental or quasi-experimental research; 3) the dependent variable is the students' 21st-century skills and the independent variable is the problem-based learning model based on REACT; 4) The research has data that can be calculated the effect size value and standard error. Data analysis is quantitative analysis with the help of the JSAP application. The results of this study show that the average effect size value is 1.078 with very high criteria. This finding concludes that the REACT-based problem-based learning model has a significant effect on students' 21st-century skills. The REACT-based problem-based learning model makes students more active and easy to understand learning concepts.